LINGUOCULTURAL CHARACTERISTICS OF LINGUISTIC UNITS OF “PROPERTY-MULK” IN ENGLISH AND UZBEK (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This scientific article describes the linguistic-cultural and linguistic-pragmatic characteristics of the lexical units related to the semantics of "property-mulk". Also, the differences and similarities of these lexical units in both languages are emphasized and enough examples are given.